Effects of sublethal fipronil insecticide concentrations on fitness and abundance profile of endosymbiont microbial species Nilaparvata lugens - AWALUDDIN AWALUDDIN; DADANG DADANG; RULY ANWAR; GIYANTO GIYANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Awaluddin, Dadang, Anwar R, Giyanto. 2024. Effects of sublethal fipronil insecticide concentrations on fitness and abundance profile of endosymbiont microbial species Nilaparvata lugens. Biodiversitas 25: 998-1006. Fipronil is a widely used active ingredient for controlling Nilaparvata lugens Stal. (Hemiptera: Delphacidae), but the effect exerted on fitness ratio and composition of endosymbiont microbes remain unknown. Therefore, this study aimed to investigate effects of insecticide by assessing fitness ratio and bacterial composition of endosymbionts in N. lugens before and after applying sublethal fipronil concentrations. A pair of LC15-equivalent fipronil-treated imago were introduced into treatment pots planted with rice 30 days after transplanting. Additionally, N. lugens endosymbionts were identified using full-length primers 27F and 1492R targeting the 16S rRNA gene. The results showed that fipronil application increased the total number of nymphs and fitness ratio of N. lugens in both IR64 and ciherang rice varieties. Similar observations were obtained with erythromycin application, although the differences were not statistically significant compared to the control. Fipronil application tended to cause an insignificant increase in the percentage of hatched eggs, while samples lacking this treatment contained abundant quantities of an endosymbiont, Acinetobacter soli. After applying insecticide, a significant alteration occurred in the composition of endosymbionts, with a substantial increase in Delftia acidovorans and D. lacustris, which both contributed to the enhanced fitness and tolerance of N. lugens to fipronil. These results showed the intricate interactions between bacteria and insects, as well as the mechanisms underlying insecticide resistance, thereby providing valuable insights for the development of new pest management strategies.